The negative derivative feedback controller tuning for vibration suppression - Puzyrov, V.; Losyeva, N.; Savchenko, N.; Termenzhy, D. (My University, 2025)
This paper investigates the problem of suppressing vibrations induced by external harmonic excitation using a Negative Derivative Feedback Controller (NDFC). The relevance of this topic is driven by the growing demand for improved vibration control in lightweight and highly flexible engineering structures, which are increasingly used in aerospace, mechanical, and civil applications. Such structures are particularly sensitive to resonance phenomena due to their low inherent damping, leading to performance degradation and potential failure. A simplified single-degree-of-freedom (DoF) model of the main structure with an attached NDFC is considered. Two independent analytical procedures for tuning the controller are proposed, aimed at ensuring effective vibration mitigation. These procedures allow for a straightforward identification of optimal regions in the parameter space, particularly with respect to damping and cut-off frequency. The use of the NDFC provides an efficient means for passive vibration suppression. Numerical simulations confirm the effectiveness of the proposed methods and demonstrate good agreement with analytical predictions. The results contribute to the advancement of vibration control strategies, offering a practical and computationally accessible approach for enhancing the dynamic performance of flexible structures.
Keywords: Negative derivative feedback controller; stability; frequency-amplitude dependence; peak responses